Effect of Different Heel Heights on Pelvic Inclination and Low Back Pain Postnatally (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted to determine the effect of different heel heights on pelvic inclination and low back pain postnatally. Forty postnatal women complained of low back pain participated in this study. They were selected randomly from physical therapy department in Al Zahraa University Hospital in Cairo, Al Azhar University. This study was conducted from January 2019 to June 2019. All women were complaining from postnatal low back pain. They were one month post partum. Their ages ranged from 25 to 35 years old. Their body mass index was not exceeding 30 kg/m2. They did not receive any medical treatment during the research period. Women with musculoskeletal disorders as disc prolapse, spondylosis, lumbar canal stenosis and spondylysthesis, history of any medication affects back pain or pelvic pain, history of any back trauma, history of any surgery in the back region or the lower extremities and body mass index exceeding 30 kg/m2 are excluded from the study. They were divided randomly into two groups equal in number, group A: women wore shoes of 3 cm heel height for three months and performing daily living activities, work stations and outdoor market visiting while group B: women wore shoes of 7 cm heel height for three months and performing daily living activities, work stations and outdoor market visiting. Visual analogue scale (VAS) was used to measure pain intensity, Oswestry Disability Questionnaire was used to assess functional disability and Palpation Meter was used to measure pelvic inclination angle for both groups (A&B) before and after wearing shoes of different heel heights. Results of this study found that, within groups there was a statistically highly significant increase (p < 0.001) in low back pain intensity, functional disability and pelvic inclination angle in both groups (A&B) after wearing different heel height. Between groups theobtained results showed that there was no significant difference between both groups A and B in low back pain intensity, functional disability and pelvic inclination angle pre wearing heel height. But post wearing heel height, there was highly significant difference between both groups A and B in low back pain intensity, functional disability and pelvic inclination angle (more increase in group B). Accordingly, it is most important for women to change their life style especially postnatal and wearing low heel shoes less than 3 cm to decrease low back pain intensity, functional disability and pelvic inclination angle.